Kekuatan Pembuktian Alat Bukti Elektronik Dalam Perkara Pidana di Indonesia - Wulandari, Laely (RETORIKA: Journal of Law, Social, and Humanities, 2024)
This study aims to 1) analyze the evidentiary power of electronic evidence in criminal cases, and 2) examine its implications for legal certainty and the protection of the defendant's rights. The type of research used is normative legal research. The approaches used are the statutory approach and the conceptual approach. The legal material for this study was obtained from related primary, secondary, and tertiary legal materials. The analysis was conducted using grammatical, systematic, and teleological interpretations, as well as examining relevant legal theories and legal principles. The results of the study indicate that electronic evidence is legally recognized and has the same evidentiary power as conventional evidence, as long as it meets the requirements of authenticity, integrity, and applicable legal procedures. The correct application of electronic evidence not only strengthens the evidence in criminal cases but also increases legal certainty and protects the rights of the defendant. The findings of this study provide a normative contribution to criminal justice practices in the digital era by ensuring the effective, legitimate, and fair application of electronic evidence, while simultaneously strengthening legal certainty and protecting the rights of the defendant.